2023
DOI: 10.32471/exp-oncology.2312-8852.vol-42-no-3.14873
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the efficacy of definitive chemoradiation therapy and surgery followed by adjuvant radiation therapy in advanced-stage oral tongue cancer

Abstract: Summary. The aim of the study was to compare the efficacy of definitive chemoradiation therapy (CRT) and primary surgery followed by adjuvant radiotherapy (RT) or CRT in the management of patients with stage III–IVA–B resectable oral tongue squamous cell carcinoma (OTSCC). Materials and Methods: It is a retrospective analysis of the treatment outcomes of 211 patients with stage III–IVA–B resectable OTSCC. The patients were divided into two groups depending on the treatment modality: 114 patients received surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In a randomized trial comparing surgery and adjuvant RT versus concurrent CRT in patients with advanced head and neck cancer, the subset analyses demonstrated that survival was significantly poorer in patients with oral cavity SCC who underwent CRT than in those who underwent surgery and RT (12% versus 68%, 5-year disease-specific survival; p = 0.038) [ 18 ]. Another comparative analysis also showed that the 5-year OS after definitive CRT in resectable stage III–IV tongue SCC was significantly inferior to that after primary surgery with adjuvant RT or CRT (20.4% vs. 57.0%) [ 19 ]. Therefore, surgery has been the standard treatment for locally advanced tongue cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized trial comparing surgery and adjuvant RT versus concurrent CRT in patients with advanced head and neck cancer, the subset analyses demonstrated that survival was significantly poorer in patients with oral cavity SCC who underwent CRT than in those who underwent surgery and RT (12% versus 68%, 5-year disease-specific survival; p = 0.038) [ 18 ]. Another comparative analysis also showed that the 5-year OS after definitive CRT in resectable stage III–IV tongue SCC was significantly inferior to that after primary surgery with adjuvant RT or CRT (20.4% vs. 57.0%) [ 19 ]. Therefore, surgery has been the standard treatment for locally advanced tongue cancer.…”
Section: Discussionmentioning
confidence: 99%